Students’ Perspective on E-Learning Through Google Classroom for Teaching English at SMK Negeri 1 Parepare - Mutmainnah; Hatta, Khairunnisa (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2018)
This research describe about career exploration technique in improving the students writing ability of the tenth year students of SMA Negeri 3 Parepare. The use of this technique was chosen as the alternative way in teaching writing. Career Exploration is an activity, guide, and counseling to assist students make decisions about choosing their future professions, and how to get jobs in their chosen fields. The objective of the research is to find out whether or not career exploration technique can improve the writing ability of the tenth year students of SMA Negeri 3 Parepare. In this research the researcher used quasi experimental method, with two group pre-test and post-test design. The population was the tenth year students of SMA Negeri 3 Parepare. The samples were drawn by using random sampling technique that consisted of 49 students which were class X.5 as experimental class and class X.6 as control class. After analyzing the research data, where the data of students‟ writing ability were analyzed by using writing ability assessment from Weigle‟s book. The result of the data analysis shows the improvement students‟ writing ability. It was showed by the mean score in pre-test was 62.29 and in post-test was 75.62. It showed that career exploration technique can improve the writing ability of the tenth year students of SMA Negeri 3 Parepare significantly. Besides, the mean score of the students in post-test (75.62) was higher than the standard scoring Departemen Pendidikan Nasional Republik Indonesia (70.00). After analyzing the data by using the t-test formula, the result of t-test value in post-test was (4.049) and t-table value was (2.012). Those indicated that H1 was accepted and H0 was rejected. It meant that career exploration technique can improve the writing ability of the tenth year students of SMA Negeri 3 Parepare significantly.